Education and the probability of being poor in Peru - Quiroz Vera, Eduardo Fernando (2017)
The main objective of this research is to analyze the educational, de-mographic, geographic, labor market, housing, income and wealth factors related to the head of household and poverty through a logit model, trying to explain the probability of being monetary poor. For this, the data collected by the 2016 National Household Survey conducted by INEI was analyzed. Through the first logit model, it is found that education -due to its effects on productivity and income generation- is a key instrument in the policy of overcoming poverty, since the higher the level achieved in their studies, the greater the reductions in the probability of being poor; in particular, it is found that concluding university means reducing the probability of being poor by 14.1 percentage points, with respect to an individual who concludes secondary school, while concluding a technical career means reducing the probability of being poor by 9 percentage points with respect to an individual who concludes secondary school. The second logit model demonstrates the importance of education in the probability of being poor, but that it alone cannot exhibit positive returns if the design of public policies is not efficient and does not consider some aspects such as demographics, labor, property, geography and housing, which also explain the probability of being poor.